Comparative characteristics of growth of the scales from pink salmon in returns to Sakhalin Island (southeast coast) and Iturup Island in 2017 and 2018 - A. M. Kaev; L. V. Romasenko; D. A. Kaev (Известия ТИНРО, 2020)
Iturup Island (in southern Kuril Islands) and southeastern Sakhalin Island are known by the highest catches of salmons within the Sakhalin-Kuril region. The timing of pink salmon mass return to Iturup is 5–10 days later than to Sakhalin, and the females returned to Iturup have higher relative individual fecundity, on average. In 2014, an unexpected increase of pink salmon catches occurred on southeastern Sakhalin Island, with a simultaneous sharp decrease of the catches on Iturup Island. Assumption on appearance of Kuril pink salmon in the Sakhalin waters was confirmed by analysis of the scale parameters (number of sclerites and intercirculi distance in the first-year scale zone), dynamics of catches, and individual fecundity of females. Sharp opposite changes of the pink salmon catch dynamics were noted again for these areas in 2017 and 2018. Such changes of pink salmon abundance could be reasoned by environmental conditions of reproduction in these areas or new redistribution between two areas. To clarify the issue, complex analysis (same as for 2014) was applied for pink salmon at southeastern Sakhalin and Iturup in 2017 and 2018 (187 and 215 fish samples from Sakhalin and 194 and 152 fish samples from Iturup in these two years, respectively). The results were interpreted following the hypothesis of fluctuating stocks. Taking into account the complex of traits, there is concluded that the assumption about redistribution of pink salmon between southeastern Sakhalin and Iturup Island in 2017 and 2018 is untenable.